Liquid clues: tracking early-stage breast cancer with ctDNA - a mini review - Easaw, Saumya; Hsu, Johann; Steuerwald, Nury; Heeke, Arielle L. (Frontiers in Oncology, 2025)
Circulating tumor DNA (ctDNA) is a testing modality that has several potential applications in the management of non-metastatic breast cancer. In this mini review, we discuss its role in early detection, treatment response assessment, and surveillance for minimal residual disease (MRD). We also review technological advances that may increase assay sensitivity. Finally, we highlight key prospective therapeutic intervention trials that evaluate the incorporation of ctDNA into clinical management of early breast cancer.